TRAFFIC LIGHT OR ROUNDABOUT? ANALYSIS USING GODUNOV METHOD TRAFFIC FLOW EQUATION - BUNAWAN (NIM : 10108096) ; Pembimbing : Dr. Sri Redjeki Pudjaprasetya, JOHAN
This final project review traffic flow issues as a continuum to use conservation equations with variable density of traffic. The orde-1 conservative discretization, known as Godunov method, applied to simulate exact solution of Riemann problems in a variety conditions such as traffic congestion is increasing or the unravel of the congestion when the obstacles in front opened. Furthermore, the resulting numerical code is used to compare the performance of traffic lights and roundabouts. The criteria used are the queue length and density of the queue.